2013
DOI: 10.1371/journal.pone.0054527
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Receptor Subunit and Calmodulin Kinase II Expression, with and without T Maze Training, in the Rat Hippocampus following Bilateral Vestibular Deafferentation

Abstract: Many previous studies have shown that lesions of the peripheral vestibular system result in spatial memory deficits and electrophysiological dysfunction in the hippocampus. Given the importance of glutamate as a neurotransmitter in the hippocampus, it was predicted that bilateral vestibular deafferentation (BVD) would alter the expression of NMDA and AMPA receptors in this area of the brain.MethodsThe expression of the NR1, NR2A, NR2B, GluR1, GluR2, GluR3 and GluR 4 glutamate receptor subunits, as well as calm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
(76 reference statements)
0
17
0
Order By: Relevance
“…Fragmentary data reported an increase in membrane NMDA receptor density within the hippocampus one month after bilateral chemical lesion , and a modulation of NMDA receptor subunits after surgical unilateral vestibular lesion in rats (Liu et al, 2003). However Zheng et al (2013), did not find same change in NMDA receptor subunits in hippocampus following bilateral vestibular lesion. In this study, we raised the question whether or not the endogenous levels of cAMP and the hippocampo-striatal ratio where influenced by the loss of vestibular lesion.…”
Section: Figurementioning
confidence: 89%
“…Fragmentary data reported an increase in membrane NMDA receptor density within the hippocampus one month after bilateral chemical lesion , and a modulation of NMDA receptor subunits after surgical unilateral vestibular lesion in rats (Liu et al, 2003). However Zheng et al (2013), did not find same change in NMDA receptor subunits in hippocampus following bilateral vestibular lesion. In this study, we raised the question whether or not the endogenous levels of cAMP and the hippocampo-striatal ratio where influenced by the loss of vestibular lesion.…”
Section: Figurementioning
confidence: 89%
“…It is often said that a patient ‘stops walking when talking' [67,68]. Also spatial learning and memory are affected by loss of labyrinthine input, probably influenced by the hippocampus, which is subject to functional and structural changes [52,69,70]. A bilateral atrophy of the hippocampus was found in 17% of a BVH population, which correlated with spatial memory deficits [71,72].…”
Section: Challenges In Establishing a Diagnosis Of Bvhmentioning
confidence: 99%
“…Rosinha et al () observed intense labeling for GluR1 and GluR2/3 in the V‐complex, which also displays high densities of AMPA receptors (Herold et al, ). Both GluR1 and GluR2/3 are also highly expressed in pyramidal cells of the mammalian hippocampus and in DG (Coultrap et al, ; Zheng et al, ). Furthermore, the high immunoreactivity for GluR4 detected in rounded neurons in DM showed comparable densities to the CA fields of the mammalian hippocampus (Wang et al, ; Rösch et al, ).…”
Section: Anatomy Of the Avian Hfmentioning
confidence: 99%